2016
DOI: 10.1007/s12975-016-0498-y
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Docosahexaenoic Acid Treatment Combined with Dietary Supplementation of Omega-3 Fatty Acids Promotes Long-Term Neurovascular Restoration After Ischemic Stroke

Abstract: Prophylactic dietary intake of omega-3 polyunsaturated fatty acids (n-3 PUFAs) has been shown to remarkably ameliorate ischemic brain injury. However, the therapeutic efficacy of n-3 PUFA administration post stroke, especially its impact on neurovascular remodeling and long-term neurological recovery, has not been fully characterized thus far. In this study, we investigated the effect of n-3 PUFA supplementation, as well as in combination with docosahexaenoic acid (DHA) injections, on long-term stroke outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 76 publications
1
24
0
1
Order By: Relevance
“…In the current study, we extended the first injection of DHA to 2 h after reperfusion and further elevated brain n-3 PUFA levels in long term by FO dietary supplementation at 5 days after MCAO. Consistent with our recent finding that delayed DHA and FO treatments after MCAO promote cognitive recovery [25], the present study demonstrates long-term beneficial effect of n-3 PUFAs on white matter integrity and microglial responses. While DHA injections alone elicited some improvement in post-stroke histological and functional outcomes, such as improved sensorimotor recovery (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the current study, we extended the first injection of DHA to 2 h after reperfusion and further elevated brain n-3 PUFA levels in long term by FO dietary supplementation at 5 days after MCAO. Consistent with our recent finding that delayed DHA and FO treatments after MCAO promote cognitive recovery [25], the present study demonstrates long-term beneficial effect of n-3 PUFAs on white matter integrity and microglial responses. While DHA injections alone elicited some improvement in post-stroke histological and functional outcomes, such as improved sensorimotor recovery (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Our recent study revealed beneficial effects of post-stroke DHA injections combined with FO dietary supplementation against stroke-induced cognitive decline [25]. In the present study, we investigated whether the delayed DHA and FO treatments ameliorate long-term sensorimotor deficits after ischemic stroke (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important restorative mechanism is oligodendrogenesis, which is essential for remyelination and white matter repair after TBI 49 . Following ischemic brain injury, delayed n-3 PUFA administration is capable of promoting angiogenesis and oligodendrogenesis, which are associated with improved functional recovery 50,51 . In the present study, we noticed an enhancement of post-TBI angiogenesis and oligodendrogenesis upon n-3 PUFA treatment that lasted up to 35 days after injury.…”
Section: Discussionmentioning
confidence: 99%
“…Brain tissue was prepared and subjected to immunohistochemistry staining as before [32ā€“33]. Primary antibodies include goat anti-CD206 (1:100; R&D System, Minneasolis, MN, USA), rabbit anti-Iba1 (1:1000, Wako, Richmond, VA, USA), F4/80 (1:200, Biolegend).…”
Section: Methodsmentioning
confidence: 99%